A participatory study of college students’ mental health during the first year of the COVID-19 pandemic - Park, Chulwoo; McClure Fuller, Melissa; Echevarria, Thea Marie; Nguyen, Kim; Perez, Daisy; Masood, Hufsa; Alsharif, Tasneem; Worthen, Miranda (Frontiers in Public Health, 2023)
The COVID-19 pandemic has negatively impacted college students’ mental health and wellbeing. Even before the pandemic, young adults reported high mental health morbidity. During the pandemic, young adult college students faced unprecedented challenges, including campus closure and a pivot to fully online education. This study employed a novel participatory approach to a Course-based Undergraduate Research Experience (CURE) in an introductory epidemiology course to examine factors students considered important regarding their experience during the pandemic. Two groups of undergraduate students enrolled in this course (one in Fall 2020 and another in Spring 2021) and participated in the CURE. A sub-group of these students continued after the class and are authors of this article. Through repeated cross-sectional surveys of college students’ peer groups in northern California in October 2020 and March 2021, this student/faculty collaborative research team evaluated depression, anxiety, suicidal ideation and several other topics related to mental health among the students’ young adult community. We found a high prevalence of anxiety (38.07% in October 2020 and 40.65% in March 2021), depression (29.85% in October 2020 and 27.57% in March 2021), and suicidal ideation (15.94% in October 2020 and 16.04% in March 2021). In addition, we identified the significant burden of loneliness for college students, with 58.06% of students reporting feeling lonely at least several days in the past two weeks. Strategies that students used to cope with the pandemic included watching shows, listening to music, or playing video games (69.01%), sleeping (56.70%), taking breaks (51.65%), and connecting with friends (52.31%) or family (51.21%). Many reported distressing household experiences: more than a third reporting loss of a job or income (34.27%) in the first year of the pandemic. We explain the participatory research approach and share empirical results of these studies. We found this participatory CURE approach led to novel, experience-based research questions; increased student motivation; real-world benefits such as combatting imposter syndrome and supporting graduate school intentions; integration of teaching, research, and service; and development of stronger student-faculty relationships. We close with recommendations to support student wellbeing and promote student engagement in research.